The Effectiveness of Animation And Comics As Educational Media For Preventing Stunting In Adolescent Girls In The West Cilandak Village South Jakarta - Lidya, Nurul; Antaria, Abdullah; Syarifah, Rosita; Juariah, Juariah (International Journal of Health Sciences, 2024)
Adolescent girls have a strategic role in stunting prevention because they are future mothers who need to understand the importance of nutrition since pregnancy. Although the national stunting prevalence in Indonesia reached 21.6%, this figure is still above the target of 14% by 2024. This study uses a quasi-experimental method without a control group to evaluate the effectiveness of animation and comic media as a means of stunting prevention education for adolescent girls in Cilandak Barat Village. The author gave An animation video to the first group, and the second group was given comics with the same educational content. Observation was carried out for 3 months, and the study results showed an increase in knowledge in the animation group by 1.04 and in the comic group by 1.40. In addition, there was an increase in attitude in the animation group by 2.20 and in the comic group by 1.56. The analysis showed a significant difference in attitude before and after the intervention with a p-value of 0.000 (<0.05). In conclusion, animated video media is more effective in increasing the understanding and attitude of adolescent girls toward stunting prevention than comic media.